Multimodal analysis of muslimah cosmetic billboards / Nor Atifah Mohamad … [et al.] - Mohamad, Nor Atifah; Suyurno, S. Salahudin; Maulan, Sumarni; Razali, Nazarul Azali (2017)
Billboard is an advertising space that is used to capture the attention of passing motorists. It is constantly visible at all time and every day of the week. Due to the distinguish nature of the billboard together with its conspicuousness, passing motorists will not be able to avoid but to notice or accept the products, services or values transferred by the billboards. Hence, this impactful power of billboard must not be taken for granted especially the one that is related to Islamic teachings or beliefs. Therefore, this paper investigates the values portrayed by muslimah cosmetic billboards. The analysis includes a discussion of the composition of the muslimah cosmetic billboards through multimodal elements. The findings reveal that a specific mode of communication relay certain values that may change muslimah perception of cosmetics products and beauty. Based on the results, this article concludes that billboard advertisement is a potent medium in transforming the concept of beauty and modesty among muslimah.